2011
DOI: 10.1161/circulationaha.111.038968
|View full text |Cite
|
Sign up to set email alerts
|

Association of Incident Cardiovascular Disease With Periodic Limb Movements During Sleep in Older Men

Abstract: Background Periodic limb movements during sleep (PLMS) cause repetitive sympathetic activation and may be associated with increased cardiovascular risk. We hypothesized that PLMS frequency (PLMI) and PLMS arousal frequency (PLMAI) are predictive of incident cardiovascular disease, including coronary heart disease (CHD), peripheral arterial disease (PAD) and cerebrovascular disease (CBD) in an elderly male cohort. Methods and Results 2,911 men in the observational MrOS sleep study cohort underwent in-home pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
114
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 166 publications
(115 citation statements)
references
References 36 publications
0
114
0
1
Order By: Relevance
“…Detailed descriptive statistics are not presented in this short note, but characteristics of similar study samples can be found in previous publications. 2,3,11 After multivariable adjustment, the rate of increase in Trails B test time (decline in function) was significantly greater for those with a PLMI ≥ 30, whereas the rate of decrease in 3MS scores was smaller, but not significant, for those with a PLMI ≥ 30. The adjusted increase in Trails B test completion time over 3.4 y were 3.5, 6.3, and 8.1 sec for PLMI category of < 5, 5 to 30, and ≥ 30, respectively (P for trend = 0.02); adjusted decline in 3MS score for PLMI categories were 1.3, 0.9, and 1.0 points over 3 y, respectively (P for trend = 0.23).…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Detailed descriptive statistics are not presented in this short note, but characteristics of similar study samples can be found in previous publications. 2,3,11 After multivariable adjustment, the rate of increase in Trails B test time (decline in function) was significantly greater for those with a PLMI ≥ 30, whereas the rate of decrease in 3MS scores was smaller, but not significant, for those with a PLMI ≥ 30. The adjusted increase in Trails B test completion time over 3.4 y were 3.5, 6.3, and 8.1 sec for PLMI category of < 5, 5 to 30, and ≥ 30, respectively (P for trend = 0.02); adjusted decline in 3MS score for PLMI categories were 1.3, 0.9, and 1.0 points over 3 y, respectively (P for trend = 0.23).…”
Section: Resultsmentioning
confidence: 96%
“…There are a few potential mechanisms. PLMS has been associated with increased sympathetic activity, elevated blood pressure and incident cardiovascular diseases, 3,20 which all contribute to vascular-related cognitive impairment, as featured by impairment in executive function. [21][22][23] Moreover, dopamine deficit, as a frequently suggested cause of PLMS, 4 also plays a key role in neurodegeneration and affects particularly the prefrontal cortex area, which regulates executive function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Measurements of physiologic components other than breathingincluding sleep disruption, heart rate variability, or periodically occurring limb movements-have been shown to track with hypertension and cardiovascular disease [15][16][17]. Previous research, however, has not adequately integrated these diverse physiologic measures to evaluate potential cardiovascular associations in a combined approach; instead, most studies have focused on singular measures, usually AHI.…”
Section: A Recent Institute Of Medicine Report Entitled 'Sleep Disormentioning
confidence: 99%
“…This chain of events is most probably under the general control of a common mechanism, i.e., "the cyclic alternating pattern," which has been shown to have a gating control function on the generation of PLM. 9,10 The recently reported association of incident cardiovascular disease with PLM during sleep in a large cohort of community dwelling elderly men living in the US, 11 and the increased mortality risk in patients with systolic heart failure and PLMI ≥ 5, 12 emphasize the need for further studies addressing the possible mechanisms by which PLM could be involved in the pathogenesis of cardiovascular disorders. …”
mentioning
confidence: 99%